A study of the dynamics and structure of the dielectric anomaly within the molecular solid TEA(TCNQ)2. Issue 12 (11th March 2022) - Berlie, Adam; Terry, Ian; Szablewski, Marek; Telling, Mark; Apperley, David; Hodgkinson, Paul; Zeller, Dominik
Abstract : The high temperature dielectric transition within the organic functional material, TEA(TCNQ)2, is studied. Both the structure and dynamics of this transition has been mapped out. Abstract : With rising interest in organic-based functional materials, it is important to understand the nature of magnetic and electrical transitions within these types of systems. One intriguing material is triethylammonium bis-7, 7, 8, 8-tetracyanoquinodimethane (TEA(TCNQ)2 ) where there is an order–disorder transition at ∼220 K. This work focuses on novel neutron scattering techniques to understand the motion of the TEA cations at this transition and explain why we see the dielectric behaviour and possible ferroelectricity within this type of system. We show that the motion of the methyl groups of the TEA cation is spatially restricted below 220 K, whereas above the dielectric anomaly at 220 K, they are free to re-orientate, which ultimately leads to some rich behaviour that could be further exploited. Lastly, we also study the dynamics at this transition using a variety of additional techniques, helping to provide a consistent picture of the motions of the cations.